Effect of Chiropractic Care on Auditory Attention in Healthy Individuals: An Analysis of the P300 Event-Related Potentials Component - Begum, Tahamina; Bliese, Courtney; Drake, Emily; Sliwka, Margaret; Sullivan, Stephanie; Reza, Mohammed Faruque (Malaysian Journal of Medical Sciences, 2026)
Background: The effect of chiropractic care on auditory attention, as measured by event-related potentials (ERP), has not been examined in healthy young adults. This study aimed to assess the impact of a single chiropractic session on auditory attention by analysing the amplitude and latency of the P300 ERP component within the auditory oddball paradigm in healthy adults.Methods: Twenty-eight healthy adults participated in this chiropractic intervention study. ERP experiments were performed both before (pre-group) and one week after (post-group) a single chiropractic care session. During the experiments, a 64-channel electroencephalography (EEG)/ERP cap was used, and participants silently counted the target tone while disregarding standard tones. The amplitude and latency of the P300 ERP component were analysed using a standardised 10–20 EEG system across 19 electrode channels. A non-parametric Wilcoxon Signed-Rank Test (pairwise) was used to compare data groups.Results: The topographic map distribution revealed a widespread pattern during standard stimuli and a more localised pattern during target stimuli in the post-group than in the pre-group. Significantly higher P300 amplitudes were observed at Cz (P = 0.013) and O1 (P = 0.012), along with a significantly shorter P300 latency at P7 (P = 0.042) in the post-group than in the pre-group.Conclusion: Higher P300 amplitudes and shorter P300 latencies indicated improved attention. This evidence suggests that chiropractic care may enhance auditory attention in healthy individuals. However, its clinical importance remains uncertain. Therefore, it is premature to recommend chiropractic care as a treatment for boosting auditory attention.